Multiplicando os pontos de vista sobre a violência nas escolas: estudo comparativo do clima escolar em duas escolas públicas de Belo Horizonte - Paulo Roberto da Costa (2005)
The present work contains the results of research carried through in two public schools of Belo Horizonte, selected, among others, for having been target of direct and systemize interventions of the City department of Education, in function of the violence indices that presented. Using information of the data base of the Command of Military Police, that contains the registers of the police occurrences in schools of all the region metropolitan of Belo Horizonte; of the surveys made for the project Rede pela Paz and, still, the direct observation and the enquiry in these two establishments, we develop a comparative analysis whose main objective was to investigate as the School´s Climate would be intervening with the perception of the students and teachers concerning the violence in its schools and the possible impacts of the unreliability feeling on the performance of these actors. It enters the components of the School´s Climate we analyze the localization; the adequacy of the physical installations; the leadership of the school; the relations between the students and these and the professionals who act there, searching to understand as these agents perceive and interact with the violence in half pertaining to school. It was of extreme importance to collate the Indices of the School´s Climate with the educational pointers supplied by the data of the SAEB and the SIMAVE, that in inform on the social-economic conditions of the studentls and the characterization to them of the establishments in relation to its efficiency in the learning, therefore this made possible to place to the test some hypotheses found in literature on the violence in the school´s environment.